Taking PISA Seriously: How Accurate are Low-Stakes Exams? - Akyol, Pelin; Krishna, Kala; Wang, Jinwen (Journal of Labor Research, 2021)
PISA is seen as the gold standard for evaluating educational outcomes worldwide. Yet, being a low-stakes exam, students may not take it seriously resulting in downward biased scores and inaccurate rankings. This paper provides a method to identify and account for non-serious behavior in low-stakes exams by leveraging information in computer-based assessments in PISA 2015. Our method corrects for non-serious behavior by fully imputing scores for items not taken seriously. We compare the scores/rankings calculated by our method to the scores/rankings calculated by giving zero points to skipped items as well as to the scores/rankings calculated by treating skipped items at the end of the exam as if they were not administered, which is the procedure followed by PISA. We show that a country can improve its ranking by up to 15 places by encouraging its own students to take the exam seriously and that the PISA approach corrects for only about half of the bias generated by the non-seriousness.